THE INFLUENCE OF PRICE, PROMOTION, LOCATION, AND SERVICESCAPE ON CUSTOMER SATISFACTION IN PEKANBARU HOLIDAY HOTEL - Wijaya, Evelyn; Purba, Ade Wijaya (Journal of Applied Business and Technology, 2021)
The rapid growth in the service sector in this globalization era has caused intense competition in the service sector. Hotel is a company engaged in services which is currently experiencing quite rapid growth. The problem that arises in this study is the instability of the number of Holiday Hotel visitors in recent years. This study aims to determine the effect of price, promotion, location, and servicescape on customer satisfaction on Holiday Hotels. The study population was all Holiday Hotel consumers with a total sample of 150 respondents. The analysis technique used is to use multiple linear regression analysis method using the t test and F test for hypothesis testing. The results of the study stated that the variable price, promotion, and servicescape had a significant positive effect on customer satisfaction, in contrast to location variables that did not significantly influence customer satisfaction.